PERAN GURU AQIDAH AKHLAK DALAM MEMBENTUK AHLAKUL KARIMAH SISWA MTS ASSAIDIYAH NGALI BIMANUSA TENGGARA BARAT - Khairul Auliyah; Nur Hasan; Lia Nur Atiqa Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
In the current era of globalization, there are many phenomena that reduce one's morality or character. For example, many children who commit acts of crime such as murder, fraud, drugs, sexual violence against early childhood, and so forth. This research is intended to answer the questions: 1) How is the implementation of moral mercy of students in MTs Assaidiyah Ngali, 2) What is the role of aqidah morality teachers in shaping the morals of students in MTs Assaidiyah Ngali, 3) What are the supporting and inhibiting factors in the formation of morality of MTs students Assaidiyah Ngali. The approach used is descriptive qualitative, with methods of observation, interviews and documentation. The results of this study concluded that the morality of students at MTs Assaidiyah Ngali largely reflected the morality of the mercy, the role of the aqidah teacher of MTs Assaidiyah Ngali was as a guide, motivator, and facilitator. Then the supporting and inhibiting factors are the madarasah itself, the teacher, the family, colleagues and the mass media.